The Personality Assessment of Elite Indian Female Archers of Recurve and Compound Division - Journal, IMR (International Multidisciplinary Research Journal, 2014)
The main purpose of the study was to assess the personality traits of elite Indian female Archers of Recurve and Compound division. For the purpose of the study, the elite were considered those who were among top eight Archers in the final national ranking tournament followed by four national ranking events conducted by Archery Association of India.The age of the subjects were ranging from 17-35 years. Eysenck’s personality inventory was used to assess the respective personality traits. The data was analyzed by applying descriptive statistics such as Mean, Standard Deviation and coefficient of variation were applied to the data. The finding of the study showed that there was Neuroticism and Extraversion stability in the behaviour of archers of every division.